Health Education For Early Awareness in Maintaining Oral Health For Students at PPTQ Hasan Munadi Islamic Boarding School, Ponorogo, East Java: Edukasi Peningkatan Kesadaran Sejak Dini Santri Santriwati dalam Menjaga Kesehatan Gigi dan Mulut, Pondok Pesantren PPTQ Hasan Munadi, Ponorogo, Jawa Timur - Yeni Puspitasari; Sabda Alam; Febria Desi; Dian Artanty; Cinitra Anindya; Adi Cahyo; Anindita Zahratur; Bingah Fitri; Ratna Mustriana; Febriyanti Kusuma; Anita Yulviyanti; Aryo Sutowijoyo; Rangga Surya; Bandaru Rahmatari; Prima Nerito; Meirna Dewita; Khamila Gayatri (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
PPTQ Hasan Munadi is an Islamic boarding school located in Badengan District, Ponorogo, East Java. The journey to the school requires a long travel distance, with winding roads and a considerable distance from the city. This situation leads to limited healthcare facilities, particularly dental clinics, and infrequent oral health education activities in the surrounding area. As a result, many students at the boarding school have a limited understanding of the importance of maintaining oral health, including the proper techniques for brushing teeth. The aim of the health education program at Pondok Pesantren PPTQ Hasan Munadi is to provide dental and oral health education and training to students from an early age (7-9 years old). This health education program used pre-post test to asses the program’s success. Before the health education intervention, students are given a pre-test. Following this, an educational session is conducted using a lecture method supported by media such as a phantom, video, and flipchart. Next session, a post-test is administered to assess any changes in the students' knowledge about maintaining oral health. Data analysis reveals that 49% of the students had a moderate level of knowledge regarding dental and oral health before the intervention. After the educational session, there was an increase of 7.3% in the number of students who achieved a good level of knowledge. This program indicates a significant improvement in the students' knowledge regarding oral health following the educational intervention.